Effects of the Structure of TiO2 Nanotube Arrays on Its Catalytic Activity for Microbial Fuel Cell. Issue 5 (25th October 2018) - Guo, Tao; Wang, Changzheng; Xu, Ping; Feng, Cuimin; Si, Shuai; Zhang, Yajun; Wang, Qiang; Shi, Mengtong; Yang, Fengnan; Wang, Jingxiao; Zhang, Yang
Abstract: To enhance the microbial fuel cell (MFC) for wastewater treatment and chemical oxygen demand degradation, TiO2 nanotubes arrays (TNA) are successfully synthesized on Ti foil substrate by the anodization process in HF and NH4 F solution, respectively (hereafter, denoted as TNA‐HF and TNA‐NF). The differences between the two kinds of TNA are revealed based on their morphologies and spectroscopic characterizations. It should be highlighted that 3D TNA‐NF with an appropriate dimension can make a positive contribution to the high photocatalytic activity. In comparison with the TNA‐HF, the 3D TNA‐NF sample exhibits a significant enhancement in current generation as the MFC anode. In particular, the TNA‐NF performs nearly 1.23 times higher than the TNA‐HF, and near twofold higher than the carbon felt. It is found that the two kinds of TiO2 ‐based anodes have different conductivities and corrosion potentials, which are responsible for the difference in their current generation performances. Based on the experimental results, excellent stability, reliability, and low cost, TNA‐NF can be considered a promising and scalable MFC bioanode material. Abstract : Microbial fuel cells represent a promising method of harvesting renewable energy, which can turn organic wastes into electrical energy and provide a potential solution to environmental problems as well. As one kind of important electrode material, TiO2 nanotube arrays have excellent performance in both power generation and chemical oxygen removal as a result of its unique nanostructure.